Sound Body Dance Compositions: An Investigation Through IMU Sensors and Their Effects on Movement Quality - Faustino, Isadora Alonso; Gatti, Daniela (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2025: Anais Estendidos do XIX Simpósio Brasileiro de Computação Musical, 2025)
The Sound Body Dance Compositions: An Investigation Through IMU Sensors and Their Effects on Movement Quality is a field report that presents findings from interactive creative research with Inertial Measurement Units (IMUs), developed by the Núcleo Redes group, using smartphones, smartwatches, and XSens wearable sensors. It discusses how different devices influence movement qualities in dance, grounded in Laban’s Movement Analysis System and based on the authors’ personal experiences with these IMUs as sound-generating systems.